Purchasing Power Parity in the Long Run. - Abuaf, Niso; Jorion, Philippe (Journal of Finance, 1990)
This paper reexamines the evidence on purchasing power parity in the long run. Previous studies have generally been unable to reject the hypothesis that the real exchange rate follows a random walk. If true, this implies that purchasing power parity does not hold. In contrast, this paper casts serious doubt on this random walk hypothesis. The results follow from more powerful estimation techniques, applied in a multilateral framework. Deviations from purchasing power parity, while substantial in the short run, appear to take about three years to be reduced in half.